Housing management practices followed by buffalo farmers of peri-urban areas of Surat city of Gujarat (Indian Journal of Animal Production and Management, 2017)
A study was conducted purposively in peri-urban areas of Surat city of Gujarat to ascertain the housing  management practices for buffalo and data was collected from randomly selected 50 buffalo farm owners  through personal interview with the help of pre-tested structured schedule. The study revealed that majority  of respondents provided open and kutcha type houses (70%), kept their buffaloes inside the house both  during day and night (94%), constructed buffalo sheds nearby their dwelling (68%), the buffalo sheds were  oriented in east-west direction (84%), had double row system of animal housing (82%) and had optimum  sized animal house (94%). Total 96, 98, 74, 90, 86, 66, 78, 60, 90, 86, 86 and 30% of respondents had  adequate floor space, provision of sufficient light, good ventilation, cleanliness, pucca floors, slope in floors  towards back, cemented type poles, double slope type of roof, provision of any type of manger, pucca type  of manger, pucca drainage facility of urine and provided bedding materials in their buffalo sheds respectively.
Keywords: Buffalo; Housing management practices; Surat